Gamentship – An Innovative Project to Improve Entrepreneurship Competences - Paiva, Teresa (2015)
Playing games it's an activity that belongs to earlier civilizations and still continues nowadays in schools and outside the environment of classroom. All studies focus on the importance of playing no matter the age, no matter the subject. In spite of the new technologies arrival and the electronic games, board games still continue to play an important role in the developing of the human being. Play it's also, from a biologic point of view, related with the complexity abilities of men to survive. The Theory of Games appears with Jon Von Neuman in 1928 and he had showed that most of the social events related with economy and business could be interpreted by strategic games. Another important aspect is this new era that humankind is living in present days. The present social and economic crisis revel some fragility among youngsters when dealing with money and business. So, being proactive, with a truly mind set focus on always trying, never give up, should be a normal behaviour for a student. But unfortunately this is not the real world aspect. Students need to develop competences that encourage them to be entrepreneurs. We, as investigators, should integrate and teach in our classes this positive attitude. So education needs to prepare adults ready to join a diversity of offers across worldwide market. Our proposal meant to join these two important issues: play games and be an entrepreneur. In this article we focus on the necessary process to implement this project. There is a lemma that will drive us all along: better education through games, to achieve better entrepreneur students and citizens in future.